THE AUDIT OF THE QUALITY CONTROL SYSTEM WITHIN THE INFORMATION TECHNOLOGY FIELD - Dragomir, Robert Gabriel (Journal of Economic Development, Environment and People, 2017)
The present paper speaks about the audit of the quality control system. First we exposed the general framework; the importance of information technology field under the actual development and challenges of the informatics systems. Then, we presented the national and international laws which regulate the audit of the informatics systems. Thirdly, we exposed the methodology of the audit for the quality system control in IT domain, describing its stages and flux diagram. In the end we jumped at the conclusions.